Trabalho e reintegração social do egresso do sistema penitenciário cearense: uma avaliação do projeto Mãos que Constroem - Ferreira, Leandro Nobre (2020)
The Project Hands That Build, developed by the Coordinator of Social Inclusion of Prison and Egress (CISPE) linked to the State of Ceará's Penitentiary Administration Secretariat (SAP), acts directly in the process of effecting the social reintegration of the egress by promoting the work, having as a guideline the dignity of the human person under the adverse context of the prison system in Ceará. To this end, partnerships are established with public agencies aiming at inserting this public in work activities in various branches, also counting on the involvement of a multidisciplinary team for the proper monitoring and institutional articulations. The study in question was of a qualitative nature and had the general objective of evaluating the project Mãos Que Constroem in the context of social reintegration, from the perspective of its beneficiaries and implementers. The analysis of the obtained data was guided by Minayo (2009), was used. Regarding the methodological aspects, field, documentary and bibliographic research was used. The techniques used were simple observation and semi-structured interview. Regarding the instruments, the field diary, the interview script and voice recorder through cell phone stood out. The research subjects were the beneficiaries, that is, the graduates and professionals working on the project. The field research included the headquarters of CISPE, the Zoonoses Center and two prison units, which function as partner institutions. The analysis of the data obtained was guided by Bardin (1978), allowing the research to go beyond appearances through thematic analysis. As a result, it was found that the project has limited effects on the realization of social reintegration, due to a situation of rationalization of expenses that implies the reduction of the multiprofessional team, the impossibility of monitoring the beneficiaries, the mismatch between supply and demand, in addition to the failure in institutional communication between managers and the multidisciplinary team. It was also noticed that there is no dialogue between the institution and other public policies in order to offer an integrated service that can go beyond the project in question.Despite the obstacles to the full functioning of Mãos Que Constroem, such a project is configured as an instrument capable of offering opportunities for those discharged from the penitentiary system, thus reducing the social impacts resulting from prison by rescuing the dignity of the beneficiaries.